Tailoring of physical properties in highly filled experimental nanohybrid resin composites - Pick, Barbara; Pelka, Matthias; Belli, Renan; Braga, Roberto R.; Lohbauer, Ulrich (Dental Materials, 2011)
Objectives: To assess the elastic modulus (EM), volumetric shrinkage (VS), and polymerization shrinkage stress (PSS) of experimental highly filled nanohybrid composites as a function of matrix composition, filler distribution, and density. Methods: One regular viscosity nanohybrid composite (Grandio, VOCO, Germany) and one flowable nanohybrid composite (Grandio Flow, VOCO) were tested as references along with six highly filled experimental nanohybrid composites (four Bis-GMA-based, one UDMA-based, and one Ormocer®-based). The experimental composites varied in filler size and density. EM values were obtained from the "three-point bending" load-displacement curve. VS was calculated with Archimedes' buoyancy principle. PSS was determined in 1-mm thick specimens placed between two (poly)methyl methacrylate rods (Ø = 6 mm) attached to an universal testing machine. Data were analyzed using oneway ANOVA, Tukey's test (α = 0.05), and linear regression analyses. Results: The flowable composite exhibited the highest VS and PSS but lowest EM. The PSS was significantly lower with Ormocer. The EM was significantly higher among experimental composites with highest filler levels. No significant differences were found between all other experimental composites regarding VS and PSS. Filler density and size did not influence EM, VS, or PSS. Significance: Neither the filler configuration nor matrix composition in the investigated materials significantly influenced composite shrinkage and mechanical properties. The highest filled experimental composite seemed to increase EM by keeping VS and PSS low; however, matrix composition seemed to be the determinant factor for shrinkage and stress development. The Ormocer, with reduced PSS, deserves further investigation. Filler size and density did not influence the tested parameters. © 2011 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Elastic modulus; Nanoparticles; Polymerization shrinkage; Resin composite; Shrinkage stress